Resposta :
Resposta:
Confere a foto
Explicação passo-a-passo:
espero ter ajudado
![Ver imagem HAYNANKERLIN](https://pt-static.z-dn.net/files/d6b/df66e5c8de458ba7d4ff33518d0f50c0.jpg)
a) N= -4+ (-1) - (+5).(-3)-4+7.(-2)
N = - 4 - 1 - 5.(-3) - 4 - 14
N = - 5 + 15 - 18
N = 10 - 18
N = - 8
b)
N= -8. (-5)-(-7). (+2) -3 -4. (-1) + 6
N = 40 + 7.2 - 3 + 4 + 6
N = 40 + 14 + 1 + 6
N = 54 + 7
N = 61
N = - 4 - 1 - 5.(-3) - 4 - 14
N = - 5 + 15 - 18
N = 10 - 18
N = - 8
b)
N= -8. (-5)-(-7). (+2) -3 -4. (-1) + 6
N = 40 + 7.2 - 3 + 4 + 6
N = 40 + 14 + 1 + 6
N = 54 + 7
N = 61